Correlation between Religious Attitude and General Health among High School Girls - Mohsen RafeeKhah; Dina Dashti; Zahra Naqizadeh Moqari; Mahdi Esmaili Sadrabadi (Shahid Beheshti University of Medical Sciences, 2019)
For downloading the full-text of this article please click here. Background and Objective: Religion is a contributory factor in health particularly in developmental stages. Yet, few studies have been conducted in this area for teenagers. This study aimed at assessing the correlation between religious attitude and general health among high school girls. Method: Correlation method was employed in this research.                                                                                                                                                                                                                                                                       The sample included 120 female high school students aged 16.6±.52, selected from 4 different schools. Research materials included Golriz and Baraheni's questionnaire about religious attitude and General Health Questionnaire (GHQ-28). The collected data were analyzed using Pearson correlation coefficient and linear regression. In this research, all the Ethical issues were observed and authors declared no conflicts of interest. Results: The results indicate a significant relation between religious attitudes and three subscales including anxiety symptoms and sleep disorder, and social function as well as depression symptoms (p<.01). However, there was no significant relationship between the religious attitude and physical function subscale (p>.05). Conclusion: The results of the study clearly demonstrate the impact of religious attitudes on the students' general health. In other words, the general health status in individuals can be predicted by religious attitudes. For downloading the full-text of this article please click here. Please cite this article as: RafeeKhah M, Dashti D, Naqizadeh Moqari Z, Esmaili Sadrabadi M. Correlation between Religious Attitude and General Health among High School Girls. J Res Relig Health. 2019; 5(2): 50- 59. doi: https://doi.org/10.22037/jrrh.v5i2.17081.